Porcine digestible peptides improve feed intake and performance of weaning pigs - Angulo E.; Córdoba X.; Torrallardona D. (Feed manufacturing in the Mediterranean region. Improving safety: From feed to food, 2001)
A total of 180 19-day old piglets distributed in 15 pens were offered, during the pre-starter period, one of three experimental treatments with iso-nutritional amounts of either porcine digestible peptides (PDP), blood plasma or fishmeal. During the starter period, all the animals were offered a common diet. During the common starter period, the tendencies observed with the previous diets persisted and pigs on the fishmeal diet showed the slowest average daily gain, followed by pigs on the plasma group (not significant) and pigs on the PDP group (P less than 0.05). At the end of the trial, pigs offered the PDP diet had a final body weight 1 kg higher than fishmeal pigs (P less than 0.05) and 0.4 kg higher than plasma pigs (not significant). It can be concluded that PDP are an excellent protein source for weaning piglets, with better quality and palatability than fishmeal, and comparable to well contrasted protein sources like blood plasma.
3. Conference of Feed Manufacturers of the Mediterranean, 2000/03/22-24, Reus (Spain)